Crisis management for heads Academic departments (Journal of the College of Basic Education, 2022)
The task of managing crises and dealing with them is one of the tasks of great difficulty, and dealing successfully with crises requires the availability of a set of key requirements that enable the organization to manage any crisis with a high degree of effectiveness.There is no doubt that our assemblies, in light of the conditions and conditions that our country is going through, are suffering from deep tremors, and may cause a rift that cannot be repaired except with great difficulty. Therefore, it is necessary for the management of academic departments to have the ability to predict the occurrence of crises that may be exposed to them of all kinds in order to deal with them.